How Auxin and Cytokinin Phytohormones Modulate Root Microbe Interactions - Boivin, Stéphane; Fonouni-Farde, Camille; Frugier, Florian (Frontiers in Plant Science, 2016)
A large range of microorganisms can associate with plants, resulting in neutral, friendly or hostile interactions. The ability of plants to recognize compatible and incompatible microorganisms and to limit or promote their colonization is therefore crucial for their survival. Elaborated communication networks determine the degree of association between the host plant and the invading microorganism. Central to these regulations of plant microbe interactions, phytohormones modulate microorganism plant associations and coordinate cellular and metabolic responses associated to the progression of microorganisms across different plant tissues. We review here hormonal regulations, focusing on auxin and cytokinin phytohormones, involved in the interactions between plant roots and soil microorganisms, including bacteria and fungi associations, either beneficial (symbiotic) or detrimental (pathogenic). The aim is to highlight similarities and differences in cytokinin/auxin functions amongst various compatible versus incompatible associations.